Tegolophus califraxini (Keifer) (Acarina Eriophyidae), a species of mite new for Europe (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of Tegolophus califraxini (Keifer) is pointed out in Northern Italy. This species, noxious for the buds of Fraxinus excelsior L., was found for the first time in Europe.